Re-Conceptualizing Ethical Practices in Adult Education in Contemporary Society using an Ethics-Centered Practice - Mitsunori Misawa; Patricia J. Higgins (Adult Education Research Conference, 2022)
This presentation will focus on re-conceptualizing and exploring ethical practices in adult education from the previous literature on ethics and developing an ethics-centered practice for modern adult education.
Keywords: ethics; adult learning; professionalism; graduate education